2022
DOI: 10.3390/genes13091610
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptome Analysis of Slow-Twitch and Fast-Twitch Muscles in Dezhou Donkeys

Abstract: The skeletal muscle fiber profile is closely related to livestock meat quality. However, the molecular mechanisms determining muscle fiber types in donkeys are not completely understood. In this study, we selected the psoas major muscle (PM; mainly composed of oxidative-type muscle fibers) and biceps femoris muscle (BF; mainly composed of glycolytic-type muscle fibers) and systematically compared their mRNA and microRNA transcriptomes via RNA-seq. We identified a total of 2881 differentially expressed genes (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 49 publications
(68 reference statements)
1
5
0
Order By: Relevance
“…We found that the expression of miR-208b-3p and miR-499a-5p was upregulated in samples with a predominance of slow-twitch fibers. This is consistent with some previous studies performed on vertebrate species [ 33 , 34 , 35 , 36 , 37 , 38 ]. The upregulation of these muscle-specific miRNAs in slow-twitch fibers is most likely due to the increased expression of their host genes MYH7 and MYH7B , which was described earlier [ 33 ] and was confirmed by the correlation analysis in this study.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…We found that the expression of miR-208b-3p and miR-499a-5p was upregulated in samples with a predominance of slow-twitch fibers. This is consistent with some previous studies performed on vertebrate species [ 33 , 34 , 35 , 36 , 37 , 38 ]. The upregulation of these muscle-specific miRNAs in slow-twitch fibers is most likely due to the increased expression of their host genes MYH7 and MYH7B , which was described earlier [ 33 ] and was confirmed by the correlation analysis in this study.…”
Section: Discussionsupporting
confidence: 94%
“…Analysis of miRNA expression in bovine skeletal muscle by massively parallel sequencing found increased expression of miR-1, miR-133a/b and miR-206, and decreased expression of miR-208a in fast-type muscles compared to slow-type ones [ 35 ]. In recent studies, RNA sequencing has been applied to analyze transcriptomic differences and miRNA–mRNA interactions between muscles with a prevalence of fast and slow fibers in chickens, horses and donkeys [ 36 , 37 , 38 ]. In horses, the expression of miR-499 and miR-206 was elevated in muscles with a predominance of slow fibers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, several studies have employed transcriptomic analysis to identify genetic markers associated with production traits in donkeys [66][67][68][69]. Similarly, Chai et al [32] conducted transcriptomic analysis of different muscles in donkeys and discovered several genes (MYH1, MYH7, TNNC1, TNNI3, TPM3, ALDOA, ENO3, and PGK1) that were found to be associated with tenderness in donkey meat.…”
Section: Transcriptomic and Whole-genome Sequencing Analysis For The ...mentioning
confidence: 99%
“…The composition of muscle fiber types may affect meat quality by influencing the content of postmortem metabolites in livestock [ 13 ]. Troponin T3 has been identified as a potential candidate gene primarily involved in actin binding and myofibril composition [ 14 ]. A higher abundance of TNNT3 has been found in myopathy of the pectoralis major muscle in fast-growing broilers, which could be caused by a reduced supply of oxygen to the breast muscle [ 15 ].…”
Section: Introductionmentioning
confidence: 99%